2022
DOI: 10.2106/jbjs.22.00177
|View full text |Cite
|
Sign up to set email alerts
|

Pain Catastrophizing Predicts Opioid and Health-Care Utilization After Orthopaedic Surgery

Abstract: Background:Most individuals undergoing elective surgery expect to discontinue opioid use after surgery, but many do not. Modifiable risk factors including psychosocial factors are associated with poor postsurgical outcomes. We wanted to know whether pain catastrophizing is specifically associated with postsurgical opioid and health-care use.Methods:This was a longitudinal cohort study of trial participants undergoing elective spine (lumbar or cervical) or lower-extremity (hip or knee osteoarthritis) surgery be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, we found that the nonresponders with clinically relevant high levels of kinesiophobia at baseline had more severe disability status, greater pain intensity, pain catastrophizing, and more opioid use at baseline, compared to responders. Similar findings denoting a correlation between these factors have also been reported in the surgical and nonsurgical population 114,123,128–133,135,136,145–147 …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Furthermore, we found that the nonresponders with clinically relevant high levels of kinesiophobia at baseline had more severe disability status, greater pain intensity, pain catastrophizing, and more opioid use at baseline, compared to responders. Similar findings denoting a correlation between these factors have also been reported in the surgical and nonsurgical population 114,123,128–133,135,136,145–147 …”
Section: Discussionsupporting
confidence: 84%
“…A total score PCS >30 indicates clinically relevant level of catastrophizing which has been to correlate strongly with the success of musculoskeletal chronic pain and spine surgery outcomes. [112][113][114][115][116][117] Of note, the nonresponders had overall a higher total PCS at baseline with a mean of 28.52 points, in contrast to 22.13 with the responders groups, although this did not meet statistical significance. Our findings agree with Haddanny et al 100 that found a higher mean average in PCS total scores in nonresponders compared to responders.…”
Section: Pain Catastrophizingmentioning
confidence: 82%
See 2 more Smart Citations
“…The negative effects of the opioid epidemic on a military population were also on display at this year's SOMOS meeting, and SOMOS members continue to look for novel strategies for effective and opioid-sparing perioperative analgesia. Unfortunately, patients with musculoskeletal injuries and diseases in the military are just as susceptible to the dangers of the opioid epidemic as civilians, and our multidisciplinary teams are working toward identifying those patients at most risk for long-term opioid tolerance and dependence, as well as the modifiable factors that we as surgeons can identify and mitigate against [4,13].…”
mentioning
confidence: 99%